Ventriculoperitoneal shunt migration with vaginal extrusion via the fallopian tube - Spencer Lord; Tyler Robinson; Morgan Spurgas (Elsevier, 2020)
Ventriculoperitoneal shunt (VPS) malfunctions are not uncommon and can lead to complex malfunctions including worsening hydrocephalus and organ injury through migration and perforation. We report a unique case of a VPS migrating through the fallopian tube, uterus, cervix and vagina of a 6-year-old female without organ perforation. X-ray demonstrated a coiled VP catheter exiting the pelvis and point of care ultrasound showed a hyperechoic structure traversing a distended fluid filled uterus. Diagnostic laparoscopy confirmed the path of shunt migration.